Effects of multilevel governance on the design and implementation of sustainable mobility plans - Gülfem Cevheribucak (Gestión y Análisis de Políticas Públicas, 2024)
Objectives: The polycentric nature of multilevel governance structures with multiple actors interacting at different levels can facilitate sustainability transitions. This study aims to explore the impact of multilevel governance on the design and implementation of sustainable urban mobility plans within the two-tiered government structure of Sweden. Methodology: The study is based on qualitative review of the academic literature, secondary sources including review of national policy documents and empirical insights drawn from the case study of Umeå, a medium-sized Swedish city which takes part in several national, local, and transnational initiatives to accelerate sustainability transitions. The empirical data is collected through semi-structured interviews with policy experts, policymakers, transport, and urban planners who are responsible for formulation and implementation of transport policies within national and local institutions. Results: The multilevel governance of transport and sustainable urban mobility policies in Sweden produces several positive effects for design and implementation of policies. These include clear division of responsibilities among public authorities at national, regional, and local government level which helps to overcome the problems such as lack of accountability and responsibility. Conclusions: Multilevel governance of sustainable urban mobility policies in Sweden enables local authorities to have access additional resources and knowledge exchange through networks consisting of various public and private actors.